1997
DOI: 10.1097/00000539-199704000-00031
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Rocuronium-Induced Neuromuscular Block During Liver Transplantation

Abstract: The prolongation of vecuronium-induced neuromuscular block has been reported as a predictor of hepatic allograft dysfunction. This study investigates the duration of action of rocuronium, which also relies on hepatic clearance, to examine whether it also is prolonged with allograft dysfunction. Fifty-seven patients undergoing orthotopic liver transplant were given rocuronium (0.6 mg/kg) prior to allograft placement and the recovery of contraction of the orbicularis oculi muscle to a 2-Hz train-of-four stimulus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…By contrast, the CL values for the LD group (672 ± 89 g) were similar to those of healthy subjects . Since the ROC concentration for the induction of muscle relaxation is inversely related to its hepatic clearance, the magnitude of the pharmacologic effect could be used as a predictor for early graft dysfunction . The likely explanation is that surgical procedures for the HBD and LD (organ retrieval time) differed, and both the storage and ischemia time could affect ROC clearance .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…By contrast, the CL values for the LD group (672 ± 89 g) were similar to those of healthy subjects . Since the ROC concentration for the induction of muscle relaxation is inversely related to its hepatic clearance, the magnitude of the pharmacologic effect could be used as a predictor for early graft dysfunction . The likely explanation is that surgical procedures for the HBD and LD (organ retrieval time) differed, and both the storage and ischemia time could affect ROC clearance .…”
Section: Discussionmentioning
confidence: 89%
“…In previous studies, a clear delineation between ROC metabolism during the neohepatic phase of liver transplantation was not possible since ROC was administered from the beginning of surgery as an integral part of the general anesthesia protocol [42,43,50]. However, a strong correlation between ROC recovery time and function of the transplanted liver immediately after liver transplantation has been suggested [43]. A significant reduction of ROC CL was found during the neohepatic phase, when the CL values were normalized to liver size in the HBD group (1475 ± 383 g; n = 5), suggesting a loss of metabolic function for the HBD donors immediately after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The liver extracts quaternary aminosteroid neuromuscular blocking drugs; therefore, we hypothesized that the duration of action of rapacuronium might offer the clinician a pharmacodynamic probe for liver function during orthotopic liver transplantation. Rapacuronium offered some characteristics that suggest that it would be a more effective pharmacodynamic probe than vecuronium or rocuronium, which have been used previously (1)(2)(3)(4). The short duration of pharmacodynamic action of this drug could potentially give early feedback to the clinician on the status of the liver graft.…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples were drawn at intervals, and an independent laboratory analyzed plasma for both rapacuronium and ORG 9488. Rapacuronium's pharmacokinetics were characterized for 3 I t has been demonstrated that the aminosteroid neuromuscular blocking agents vecuronium and rocuronium may be used to identify primary graft dysfunction after liver transplantation by assessing their duration of clinical action (1)(2)(3)(4)(5). However, the rate of metabolism of these drugs requires a delay of at least 100 minutes before the diagnosis of primary nonfunction can be assumed likely.…”
mentioning
confidence: 99%
“…The new liver graft may be evaluated by vecuronium since the time for the return of a train-of-four (TOF) with a nerve stimulator correlates with the function of the new liver (Lukin et al, 1995). Similarly, the duration of action of rocuronium is also used for the assessment of allograft function; >150 minutes refers to allograft dysfunction (Marcel et al, 1997).…”
Section: Anesthetic Induction and Maintenancementioning
confidence: 99%